Fecal microbiota transplantation—could stool donors’ and receptors’ diet be the key to future success? - Rita Silva; Rita Silva; Liliana Dinis; Liliana Dinis; Liliana Dinis; Arnau Peris; Luís Novais; Conceição Calhau; Diogo Pestana; Diogo Pestana; Cláudia Marques; Cláudia Marques (Frontiers in Gastroenterology, 2023)
Fecal microbiota transplantation (FMT) is indicated in many countries for patients with multiple recurrences of Clostridioides difficile infection (CDI) for whom appropriate antibiotic treatments have failed. Donor selection is a demanding and rigorous process in view of the implementation of FMT programs worldwide. One of the most noteworthy factors that has been shown to affect FMT outcomes is the microbial diversity of the stool donor. A detailed assessment of the donor’s microbiota is crucial, as the microbiota is complex, dynamic, and resilient, and a healthy microbiota has several dimensions in addition to the absence of pathogens. Diet is one of the most important factors that modulates the composition and function of the gut microbiome (GM) and has a critical role in orchestrating the host–microbiota crosstalk throughout life. The diversity of the human GM seems to be related to variations in dietary patterns. Currently, the dietary patterns of stool donors and receptors are not taken into consideration in any way for FMT. In this study, we reflect on the importance of including this type of assessment in the stool donor screening process and knowing the impact of diet on the GM, as well as the importance of monitoring receptors’ diet to ensure the engraftment of the transplanted microbiota.